Wind tunnel tests on the aerodynamic characteristics of vehicles on highway bridges. Issue 13 (October 2020) - He, Xuhui; Xue, Fanrong; Zou, Yunfeng; Chen, Suren; Han, Yan; Du, Bing; Xu, Xiangdong; Ma, Baihu
Accurately quantifying the aerodynamic forces acting on vehicles and long-span bridges is critical for assessing the safety of moving vehicles on bridges which are subjected to strong wind. It is necessary to consider the aerodynamic interference between vehicles and the bridge, especially for this with the bluff body section and wind barriers. However, very few investigations have been carried out to find aerodynamic coefficients of vehicles on a bridge with the bluff body section and considering the effect of wind barrier. This article therefore carried out wind tunnel tests to determine aerodynamic coefficients of container truck on a bridge with a π-cross section and wind barriers. The influence of vehicle position in different road lanes of the bridge deck and the aerodynamic interference between vehicles on the aerodynamic characteristics of the vehicle and the bridge are investigated. Different heights and ventilation ratios of wind barrier are taken into consideration to examine variations of aerodynamic coefficients with different wind barriers. Furthermore, the change mechanism in the aerodynamic coefficients of the vehicles is observed by analyzing the wind pressure distribution on the surface of the vehicles. The test results show that the different lane locations of the vehicle affect the aerodynamic coefficients significantly, as well as the aerodynamic interference between vehicles with transverse arrangement or longitudinal arrangement, especially for the side force coefficient. The existence of wind barrier reduces the side force coefficients of the vehicle remarkably. Such effects also vary with the ventilation ratio and height of wind barrier.